2016
DOI: 10.3892/ijo.2016.3661
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of FOSB correlates with tumor progression and poor survival in patients with gastric cancer

Abstract: FOSB protein is encoded by the FOSB gene in humans, which shares structural similarities with the prototype of the Fos family. FOSB plays a role by AP-1 complex which is composed of heterodimers of Jun and Fos members. Our experiment aimed to evaluate the effect of FOSB in gastric cancer (GC) patients and then probe its significance in prognosis. We detected the expression of FOSB in GC and adjacent non-cancerous tissues by western blot analysis and real-time quantitative PCR (qRT-PCR). Moreover, we analyzed F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…As previously demonstrated, some of the fifteen genes serve crucial roles in GC [ 45 47 ]. For example, Tang et al have demonstrated that FOSB was significantly decreased in GC tissues, consistent with the results of this study, and moreover, downregulated expression of FOSB was correlated with poor prognosis for GC patients [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…As previously demonstrated, some of the fifteen genes serve crucial roles in GC [ 45 47 ]. For example, Tang et al have demonstrated that FOSB was significantly decreased in GC tissues, consistent with the results of this study, and moreover, downregulated expression of FOSB was correlated with poor prognosis for GC patients [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…TNFa gene expression was down-regulated by the knockdown of AC009283.1 and TNFa up-regulation has also been shown to increase cellular proliferation 39 . The oncogene FOSB was up-regulated after AC009283.1 knockdown, and FOSB has been associated with suppressed cell proliferation in gastric cancer cell lines 40 . In vitro assays (automated cell counting, proliferation index and cycle cell assay by flow cytometry) confirmed that knockdown of AC009283.1 reduced proliferation and decreased S phase in SKBR3 cells, potentially through the modulation of NOCTH3 , TNFa and FOSB genes.…”
Section: Discussionmentioning
confidence: 93%
“…Between the most differentially expressed and upregulated genes under hypoxia and glucose deprivation are KRT17, GADD34/PPP1R15A, ETS1, DDIT4/REDD1, HK2, PFKFB3, DDIT3, SLC2A3, TAGLN, SLC22A15, SH3D21, DEPP1, RORA, ANGPTL4, ELOVL6 , FOSB , LMNB1 , and EGR1 . Together, these constitute a panel of biotic stress activated genes driving systemic changes at the transcriptomic level towards more undifferentiated ( KRT17 , FOSB ) 30,31 , poorly proliferative ( LMNB1 ) 32,33 , and less prone to programmed cell death and anoikis ( GADD34/PPP1R15A , DDIT4/REDD1 , PFKFB3 , ANGPTL4 ) phenotypes 3437 . Moreover, the negative regulation of suppressor factors ( EGR1) 38 , allied to the promotion of immunosuppressor or tolerogenic ( GADD34/PPP1R15A, DDIT3) programs 3943 leads to enhanced invasive/migratory ( ETS1 , DDIT4/REDD1 , TAGLN ) capacities 4446 , as previously demonstrated.…”
Section: Resultsmentioning
confidence: 99%